Melatonin in regulation of inflammatory pathways in rheumatoid arthritis and osteoarthritis: involvement of circadian clock genes. (12th July 2017) - Jahanban‐Esfahlan, Rana; Mehrzadi, Saeed; Reiter, Russel J; Seidi, Khaled; Majidinia, Maryam; Baghi, Hossein Bannazadeh; Khatami, Nasrin; Yousefi, Bahman; Sadeghpour, Alireza
Abstract : Rheumatoid arthritis (RA) and osteoarthritis (OA) are the two most prevalent joint diseases. A such, they are important causes of pain and disability in a substantial proportion of the human population. A common characteristic of these diseases is the erosion of articular cartilage and consequently joint dysfunction. Melatonin has been proposed as a link between circadian rhythms and joint diseases including RA and OA. This hormone exerts a diversity of regulatory actions through binding to specific receptors and intracellular targets as well as having receptor‐independent actions as a free radical scavenger. Cytoprotective effects of melatonin involve a myriad of prominent receptor‐mediated pathways/molecules associated with inflammation, of which the role of omnipresent NF‐κB signalling is crucial. Likewise, disturbance of circadian timekeeping is closely involved in the aetiology of inflammatory arthritis. Melatonin is shown to stimulate cartilage destruction/regeneration through direct/indirect modulation of the expression of the main circadian clock genes, such as BMAL, CRY and/or DEC2. In the current article, we review the effects of melatonin on RA and OA, focusing on its ability to regulate inflammatory pathways and circadian rhythms. We also review the possible protective effects of melatonin on RA and OA pathogenesis. Linked Articles: This article is part of a themed section on Recent Developments in Research of Melatonin and its Potential Therapeutic Applications. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.16/issuetoc